The effect of the mobile “blood pressure management application” on hypertension self-management enhancement: a randomized controlled trial - Ali Bozorgi; Hamed Hosseini; Hassan Eftekhar; Reza Majdzadeh; Ali Yoonessi; Ali Ramezankhani; Mehdi Mansouri; Mahnaz Ashoorkhani (Trials, 2021)
Abstract Background Self-management of hypertension is of great significance given its increasing incidence and its associated disabilities. In view of the increased use of mobile health in medicine, the present study evaluated the effect of a self-management application on patient adherence to hypertension treatment. Methods This clinical trial was performed on 120 hypertensive patients who were provided with a mobile intervention for 8 weeks and followed up until the 24th week. Data on the primary outcome (adherence to treatment) and secondary outcomes (adherence to the DASH diet, regular monitoring of blood pressure, and physical activity) were collected using a questionnaire and a mobile application, respectively. The inter-group change difference over time was analyzed using repeated measures ANOVA (general linear model). Results The treatment adherence score increased by an average of 5.9 (95% CI 5.0–6.7) in the intervention group compared to the control group. The scores of “adherence to the low-fat and low-salt diet plans” were 1.7 (95% CI 1.3–2.1) and 1.5 (95% CI 1.2–1.9), respectively. Moreover, moderate physical activity increased to 100.0 min (95% CI 61.7–138.3) per week in the intervention group. Conclusion The treatment and control of blood pressure require a multifaceted approach given its complexity and multifactorial nature. Considering the widespread use of smartphones, mHealth interventions can be effective in self-management and better patient adherence to treatments. Our results showed that this application can be used as a successful tool for hypertension self-management in patients attending public hospitals in developing countries. Trial registration Iran Randomized Clinical Trial Center IRCT2015111712211N2 . Registered on 1 January 2016